PRESERVING AND SUSTAINING THE ENVIRONMENTAL IDENTITY OF ISLAMIC RESIDENTIAL BUILDINGS IN THE HEJAZ REGION IN KSA - Salma Dwidar; Hala Sirror; Amani Derbali (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
The Kingdom of Saudi Arabia has a rich urban and architectural legacy that dates back to the numerous eras of Islamic civilization. This study investigates the environmental influence on Ottoman-style heritage structures in the Kingdom of Saudi Arabia, particularly in the Hejaz Region. The region was chosen because of its diverse climates, which include a hot, dry environment in the middle of the Western Desert and a hot, humid climate on the Red Sea coast. Heritage buildings are examined from design, architectural, and urban perspectives to learn how environmental sustainability is achieved and to examine building materials and their sustainability. Furthermore, common architectural characteristics, systems, and designs are recognized to be integrated into modern building design for the contemporary era to maintain their design uniqueness.